2015
DOI: 10.2151/jmsj.2015-045
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Cloud Top Heights of Marine Boundary Layer Clouds and the Frequency of Marine Fog over Mid-Latitudes

Abstract: The cloud top height of marine boundary layer clouds (MBLCs) in the mid-latitudes has received less attention than that of subtropical MBLCs and is investigated here using cloud mask data, which were based on observations from the cloud-aerosol lidar and infrared pathfinder satellite observation (CALIPSO) satellite. This study provides a comprehensive overview of the observational characteristics of variations in cloud top height of MBLCs and fog frequency over the mid-latitudes. Seasonal variations in the clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…All experiments showed general increases in estimated parameter from the default value of 0.1. Figure 8 of Kawai et al, 2015). However, some inland regions near the ocean showed shifts in values due to LETKF, which assimilates observations within the localization influence radius.…”
Section: Journal Of Geophysical Research: Atmospheressupporting
confidence: 57%
See 2 more Smart Citations
“…All experiments showed general increases in estimated parameter from the default value of 0.1. Figure 8 of Kawai et al, 2015). However, some inland regions near the ocean showed shifts in values due to LETKF, which assimilates observations within the localization influence radius.…”
Section: Journal Of Geophysical Research: Atmospheressupporting
confidence: 57%
“…As LWP observations are available only over the ocean, parameter shifts were seen mainly over the ocean. Figure 10 of Kawai et al, 2015), and the stable atmosphere leads to slower autoconversion. Due to the smaller localization radius, LWP-L100km resulted in the finest parameter patterns.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
See 1 more Smart Citation
“…IGRA‐derived FTH were compared to an independent cloud altitude data set from the CALIPSO Level 2 cloud layer product at 1 km along‐track resolution (CAL_LID_L2_01kmCLay‐Standard_V4–10 from https://www-calipso.larc.nasa.gov/). CALIPSO provides vertical profiles of aerosols and clouds with a vertical resolution of 30 m (Winker et al, ) and has been found to accurately capture fog frequency and spatial distribution when no upper clouds are present (Cermak, ; Kawai et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the bulk of the observations fall above the blue line suggesting (1) that contributions from nonoceanic sources may be significant, (2) a breakdown in the approximation that instantaneous concentration and flux measurements are constant for multiple monoterpene lifetimes, and/or (3) a higher contribution of lower reactivity monoterpenes (e.g., camphene compared to α-pinene) to the total monoterpene signal. For comparison, the sustained monoterpene mixing ratios of 125 and 5 ppt, as observed by Yassaa et al [2008] in the Southern Ocean during in and out of bloom conditions, would require fluxes greater than 1.0 × 10 10 molecules cm À2 s À1 and 5 × 10 8 molecules cm À2 s À1 , respectively, for [O 3 ] = 20 ppb, [OH] 24h = 2.5 × 10 5 molecules cm À3 , MBL = 600 m [Kawai et al, 2015], comparable to that required in this study.…”
Section: 1002/2017gl072975mentioning
confidence: 99%